O processo e o produto editorial de um jornal escolar impresso: investigação acerca do letramento jornalístico de estudantes do ensino fundamental - Dutra, Giselle Bezerra Mesquita (2018)
The school newspaper can be used not only as a teaching-learning instrument of written language, but also as interactive media among students, thus providing a more effective development of their literacy. Based on this assumption, we have as the dissertation general objective to investigate the characteristics of the journalistic literacy of primary school students that compose the Clube do Jornal, in a full-time municipal public school in the city of Fortaleza. We observed the process of the school newspaper production from its publishing to its printed publicity. To achieve this goal, we adopt the concepts that Buckingham (2010) pointed to describe the media literacy: production, language, representation and audience. In this theoretical course, we also use the study on genres of Bakhtin's discourse (2003), the social literacy developed by Street (2014), as well as the ideas of Antunes (2003) on the teaching of mother tongue in school and the approaches of Baltar (2010) and Bonini (2011) on the school newspaper. Being an ethnographic qualitative research, we use as data construction techniques: participant observation of the actions developed by Clube do Jornal, semi-structured interview with two members in the management positions of the club, personal letters written by the majority of its members and, finally, sample collection of three printed editions of the school newspaper, published in 2017. As a result, we noticed that the publishing process of the newspaper does not have an effective orientation, regarding the perspective of the teachers and managers of the school. The task of producing then depends on the intuitive protagonism of the students and their inferences of what they know about the media-journalistic sphere. Thus, the production of the genres and the audience sought by the students reflect, together with the representations conveyed and with the uses they make of the written language, aspects of a language practice predominantly circumscribed to the school environment, although these subjects make significant innovations regarding process and the product of that medium. With this, we can conclude that the journalistic literacy of the Clube do Jornal’s students is still quite characterized by the values of the school culture, and it needs to be expanded in discursive possibilities in relation to the critical, social and ideological perspectives, considering the multiliteracies and through a more careful look from pedagogical agents of the school institutions.